Sexually transmitted infections in male clients of female sex workers in Benin: risk factors and reassessment of the leucocyte esterase dipstick for screening of urethral infections - Alary, M (BMJ Group, 2003)
Objectives: (1) To assess risk factors for urethral infections with Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis among male clients of female sex workers (FSWs) in Benin; (2) to study the validity of LED testing of male urine samples compared to a highly sensitive gold standard (PCR) for the diagnosis of urethral infections with the organisms cited above. Methods: Male clients of FSWs (n=404) were recruited on site at prostitution venues in Cotonou, Benin, between 28 May and 18 August 1998. A urine sample was obtained from each participant just before he visited the FSW, and tested immediately using a leucocyte esterase dipstick (LED) test. It was then tested for HIV using the Calypte EIA with western blot confirmation, and for C trachomatis, N gonorrhoeae, and T vaginalis by PCR. After leaving the FSW's room, participants were interviewed about demographics, sexual behaviour, STI history and current symptoms and signs, and were examined for urethral discharge, genital ulcers, and inguinal lymphadenopathies. Results: STI prevalences were: C trachomatis, 2.7%; N gonorrhoeae, 5.4%; either chlamydia or gonorrhoea 7.7%; T vaginalis 2.7%; HIV, 8.4%. Lack of condom use with FSWs and a history of STI were independently associated with C trachomatis and/or N gonorrhoeae infection. Over 80% of these infections were in asymptomatic subjects. The overall sensitivity, specificity, positive and negative predictive values of the LED test for detection of either C trachomatis or N gonorrhoeae were 48.4%, 94.9%, 44.1%, and 95.7%, respectively. In symptomatic participants (n=22), all these parameters were 100% while they were 47.4%, 94.7%, 37.5%, and 96.4% in asymptomatic men (n=304). Conclusions: Since most STIs are asymptomatic in this population, case finding programmes for gonorrhoea and chlamydia could be useful. The performance characteristics of the LED test in this study suggest that it could be useful to detect asymptomatic infection by either C trachomatis or N gonorrhoeae in high risk men.